Thermal behavior of iron in 6H-SiC: Influence of He-induced defects. (September 2022) - Li, B.S.; Sen, H.S.; Daghbouj, N.; AlMotasem, A.T.; Lorinčík, J.; Karlik, M.; Ge, F.F.; Zhang, L.; Sofer, Z.; Elantyev, I.; Callisti, M.; Polcar, T.
Abstract: SiC is considered a perspective material in advanced nuclear systems as well as for electronic or spintronic applications, which require an ion implantation process. In this regard, two sets of 6H-SiC samples were implanted with i) 2.5 MeV Fe ions and ii) 2.5 MeV Fe ions and co-implanted 500 keV He ions at room temperature and then annealed at 1500 °C for 2 h. The microstructure evolution and Fe diffusion behavior before and after annealing were characterized and analyzed. After annealing, Fe concentration is enhanced close to the surface in the Fe-implanted sample, whereas in the co-implanted system, Fe atoms are redistributed into two distinct, spatially separated regions (close to the surface, and around the He-induced defects). The reason behind this finding is explained from an energetic point of view by using ab initio simulations. Technologically, the pre-existing cavities can be used to control the Fe diffusion. Graphical abstract: Image, graphical abstract